Three-stage robust inverter-based voltage/var control for distribution networks with high-level PV - Zhang, Cuo (2021)
This paper proposes a novel three-stage robust inverter-based voltage/var control (TRI-VVC) approach for high photovoltaic (PV)-penetrated distribution networks. The approach aims at coordinating three different control stages from centralized to local VVC to reduce energy loss and mitigate voltage deviation. In the first stage, capacitor banks and an on-load tap changer are scheduled hourly in a rolling horizon. In the second stage, PV inverters are dispatched in a short time-window. In the third stage, the inverters respond to real-time voltage violation through local droop controllers. A new PV inverter model for voltage control is developed to support both the centralized var dispatch and the local var droop control. To address uncertain PV output and load demand, a robust optimization (RO) model is proposed to optimize the first two stages while taking into account the droop voltage control support from the third stage. A linearized distribution power flow model with power loss is developed and applied in the RO. The simulation results show high efficiency and robustness of the proposed TRI-VVC strategy.